Practice physics - Squires, G. L. (Cambridge University Press, 2001)
This classic companion to undergraduate practical work in physics describes the purposeful, critical approach that should be made to all physics experiments. It covers the statistical treatment of data and experimental methods, and gives advice on keeping efficient records, calculations, and scientific writing. The new edition features treatment of the c2 distribution, a section on atomic clocks, worked examples based on spreadsheets, and additional exercises. Existing examples and references have been brought up to date. The text is liberally illustrated with examples and exercises, with solutions to the latter